Morphology of the deltoid muscles in elite tennis players - Mavidis, A.; Vamvakoudis, E.; Metaxas, T.; Stefanidis, P.; Koutlianos, N.; Christoulas, K.; Karamanlis, A.; Mandroukas, K. (Journal of Sports Sciences, 2007)
The aim of this study was to examine the deltoid muscle properties of the dominant and non-dominant arm of Greek professional male tennis players. Eight male tennis players (mean age 22.0 years, s = 3.2) were subjected to biopsy of the deltoid muscle of both arms. Adenosine triphosphate (ATPase) histochemistry and myosin heavy chain (MHC) composition were performed on the samples with homogenate electrophoresis. No significant differences were observed in the percentage of types I, IIa, IIab, and IIb muscle fibres between the deltoid muscles of the two arms. Types I, IIa, and IIx muscle fibres of the dominant and non-dominant deltoid muscles did not differ significantly for MHC isoform composition. Type IIab muscle fibres showed a similar cross-sectional area (CSA) percentage distribution between the two arms. The CSA percentage for types I, IIa, and IIb muscle fibers did not differ significantly between the dominant and the non-dominant arm. We conclude therefore that regular tennis training probably does not lead to any significant changes in the muscle fibre types of the dominant and non-dominant arms of elite tennis players.